The effects of APOE-ε4 on the BOLD response. - Trachtenberg, A; Filippini, N; Mackay, C (2012)
In the last decade, functional magnetic resonance imaging (fMRI) has emerged as a tool to study changes in brain function associated with a genetic risk for Alzheimer's disease (AD), with a particular focus on the effects of the APOE-ε4 allele. This review compiles the existing literature concerning the effects of APOE genotype on the blood oxygen level dependent (BOLD) response, measured during task-based functional magnetic resonance imaging. While most studies report a significant difference in brain activity between carriers and noncarriers of the ε4 allele, there are inconsistencies in the direction and location of change. These inconsistencies were addressed by examining the effect of task, family history of Alzheimer's disease, and age on the relationship between APOE genotype and the BOLD response, but no clear pattern emerged. The review discusses the interpretation of BOLD differences between ε4 carriers and noncarriers, provides suggestions for future studies, and highlights important limitations of this type of research.